Treatment of Patients with Early Breast Cancer: Evidence, Controversies, Consensus - Untch, Michael; Fasching, Peter A.; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Haidinger, Renate; Huober, Jens; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Krug, David; Kühn, Thorsten; Loibl, Sibylle; Lüftner, Diana; Müller, Volkmar; Schneeweiss, Andreas; Thill, Marc; Harbeck, Nadia; Thomssen, Christoph (Geburtshilfe und Frauenheilkunde, 2021)
This yearʼs 17th St. Gallen (SG) Consensus Conference on the Treatment of Patients with Early Breast Cancer (SG-BCC) with the title “Customizing local and systemic therapies for women with early breast cancer” focused on the challenge of targeting the treatment of early breast cancer more specifically to the individual disease situation of each patient. As in previous years, a German working group of leading breast cancer experts discussed the results of the international SG-BCC 2021 in the context of the German guideline. It is helpful to compare the SG recommendations with the recently updated treatment recommendations of the Breast Commission of the German Working Group on Gynaecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie e. V., AGO) and the S3 guideline because the SG-BCC panel comprised experts from different countries, which is why country-specific aspects can be incorporated into the SG recommendations. The German treatment recommendations of the AGO and the S3 guideline are based on current evidence. Nevertheless, any therapeutic decision must always undergo a risk-benefit analysis for the specific situation and to be discussed with the patient.Die diesjährige 17. St.-Gallen-(SG-)Konsensus-Konferenz zur Behandlung von Patientinnen mit frühem Mammakarzinom (SG-BCC) stand unter dem Motto „Customizing local and systemic therapies for women with early breast cancer“ und fokussierte auf die Herausforderung, die Behandlung des frühen Mammakarzinoms zielgerichteter auf die individuelle Krankheitssituation adaptieren. Wie schon in den vergangenen Jahren hat auch dieses Jahr eine deutsche Arbeitsgruppe führender Brustkrebsexpert*Innen die Ergebnisse der internationalen SG-BCC 2021 vor dem Hintergrund der deutschen Therapieempfehlungen für den Klinikalltag in Deutschland diskutiert. Der Vergleich der SG-Empfehlungen mit den erst kürzlich aktualisierten Therapieempfehlungen der Kommission Mamma der Arbeitsgemeinschaft Gynäkologische Onkologie e. V. (AGO) sowie der S3-Leitlinie ist hilfreich, da sich das SG-BCC-Panel aus Experten unterschiedlicher Länder zusammensetzt, weshalb länderspezifische Besonderheiten in die SG-Empfehlungen einfließen können. Die deutschen Therapieempfehlungen der AGO sowie der S3-Leitlinie basieren auf der aktuellen Evidenz. Gleichwohl muss jede Therapieentscheidung immer einer Nutzen-Risiko-Abwägung für die individuelle Situation unterzogen und mit der Patientin besprochen werden.
Keywords: St. Gallen Consensus 2021; early breast cancer; surgery; radiotherapy; (neo)adjuvant systemic therapy; targeted therapy